IMPLEMENTATION OF STAD LEARNING STRATEGIES (STUDENTS-TEAM-ACHIEVEMENT-DIVISION) TO IMPROVE STUDENT'S ABILITY IN ENGLISH - Yusniarti Runggo (JURNAL EDUSCIENCE (JES), 2021)
The research aims to improve student's ability in english  by using the stad learning strategy implementation (students-team-achievement-division). The design of this research is classroom action research, in which a researcher and collaborator take part actively in the class to conduct teaching and make observations during the activity. In this study, researcher used cooperative learning type STAD or Students-Team-Achivement-Division. In the type of STAD cooperative learning, students will be divided into groups of 4-6 people who prioritize class heterogeneity in academic achievement. The researchers provided a lesson, and students in the group are expected to master the lesson. The results of the research showed that the STAD type cooperative learning is effective in improving students' ability in English. The implementation of cycle 1 and cycle 2 showed an increase in student achievement. There were 9 (45%) students who were successful and 11 (55%) of them failed. Then, the success increased to 20 (100%) students in cycle 2. In other words, all students can achieve learning achievement in cycle 2.